2012
DOI: 10.1017/s0714980812000190
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Physician Advice, Physical Activity, and Socio-demographic Groups in Older Spanish Adults

Abstract: RÉSUMÉCette étude a examiné la relation entre l'avis médicale pour s'engager dans ld'activité physique avec, le type de demande d'activité physique et les variables démographiques. Une étude transversale a été élaborécréé. Un questionnaire avec des items sur l'avis médicale, le niveau de demande pour l'activité physique, et les variables démographiques a été complété par une échantillon national de personnes âgées en Espagne (N = 933, M = 74,1, range de 65 à 93), sélectionnées de manière aléatoire à plusieurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Twenty-three studies (reported in 24 articles) examined patient factors associated with PA BI (Supplementary Table S5). 16 , 17 , 22 , 27 , 36 , 38 , 40 , 41 , 44 , 45 , 47 , 52 54 , 60 , 61 , 63 , 64 , 67 , 68 , 73 , 74 , 80 , 81 Although the majority of evidence was mixed and inconclusive, the following patient factors were most consistently reported to be significantly and positively associated with the delivery or receipt of PA BI: high patient body mass index ( n = 12); 16 , 38 , 40 , 45 , 47 , 53 , 54 , 60 , 63 , 67 , 68 , 73 physically inactive/sedentary patients ( n = 6); 38 , 47 , 53 , 54 , 60 , 67 poorer health/greater number of comorbidities ( n = 5); 38 , 53 , 60 , 67 , 73 and greater number of physician visits ( n = 4). 16 , 44 , 45 , 53 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-three studies (reported in 24 articles) examined patient factors associated with PA BI (Supplementary Table S5). 16 , 17 , 22 , 27 , 36 , 38 , 40 , 41 , 44 , 45 , 47 , 52 54 , 60 , 61 , 63 , 64 , 67 , 68 , 73 , 74 , 80 , 81 Although the majority of evidence was mixed and inconclusive, the following patient factors were most consistently reported to be significantly and positively associated with the delivery or receipt of PA BI: high patient body mass index ( n = 12); 16 , 38 , 40 , 45 , 47 , 53 , 54 , 60 , 63 , 67 , 68 , 73 physically inactive/sedentary patients ( n = 6); 38 , 47 , 53 , 54 , 60 , 67 poorer health/greater number of comorbidities ( n = 5); 38 , 53 , 60 , 67 , 73 and greater number of physician visits ( n = 4). 16 , 44 , 45 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…• greater number of physician visits (n = 4). 16,44,45,53 Patient sex 22,38,40,60,61,64,68,73 and age 22,36,38,40,60,61 were often found not to be associated with PA BI.…”
Section: Level Of Pa Screening By Health Professionalsmentioning
confidence: 98%
See 3 more Smart Citations